Nutrition Knowledge, Attitudes, and Practices among Adult Gym-goers in West Delhi, India: A Cross-sectional Study - Diksha Agrawat; Neha Bakshi; Pooja Raizada (Journal of Integrated Health Sciences, 2025)
Introduction: Poor training practices and misinformation about dietary choices may impact the overall health and performance of gym-goers. Aims: The increasing popularity of fitness centers highlights the need to assess gym-goers’ nutrition knowledge, attitudes, and practices (KAPs). Material and Methods: A cross-sectional study was carried out involving 106 gym attendees (54 men, 52 women) from six gyms in West Delhi. Nutritional KAP data were obtained by adapting the FAO questionnaire to an Indian setting. Anthropometric measurements like weight, height, and waist circumference (WC) were recorded. Dietary intake was estimated by recording the usual food intake. Results: The study found a strong positive correlation between nutrition knowledge and attitude scores (r = 0.715) and a significant association with education level (P < 0.05). Although 73.6% had high nutrition knowledge, only 66% demonstrated moderate nutrition practices, indicating a gap between awareness and behavior. Supplement use was higher among males (53.7%) than females (9.62%). While 49% met WHO physical activity guidelines, 65.38% of females had a normal body mass index (BMI), but 51.92% had central obesity. Among males, 40.74% were classified as obese by BMI, though 90.74% had a normal WC. Protein consumption was strongly correlated with increased nutrition knowledge scores (P < 0.05), whereas consumption of fat and carbohydrates was not significantly correlated with KAP scores. Conclusion: The study reveals a strong correlation between nutrition knowledge and attitudes among gym-goers but highlights a gap in translating knowledge into practice, reflecting a complex interplay between KAP. This underscores the need for targeted education programs that not only disseminate knowledge but also address motivational and behavioral barriers to effective practice.